2006
DOI: 10.1210/jc.2005-2283
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype-Genotype Correlation in Eight Chinese 17α-Hydroxylase/17,20 Lyase-Deficiency Patients with Five Novel Mutations of CYP17A1 Gene

Abstract: The clinical manifestations in patients with 17OHD correlate with CYP17A1 mutations and enzymatic activities by in vitro enzyme assay and computer modeling. F453S mutation results in partially reduced enzymatic activities and a subtle phenotype. The prevalent mutation 1517_1525del in Chinese 17OHD patients might be a founder effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 22 publications
6
28
0
1
Order By: Relevance
“…The serum steroid profile was comparable to those previously published (8,20,24,25,28) and disclosed marked increases of B, DOC and their 18-hydroxy--derivatives -18OHB and 18OHDOC -, the so-called 17-deoxysteroids (from the "mineralocorticoid pathway") of the zona fasciculata.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The serum steroid profile was comparable to those previously published (8,20,24,25,28) and disclosed marked increases of B, DOC and their 18-hydroxy--derivatives -18OHB and 18OHDOC -, the so-called 17-deoxysteroids (from the "mineralocorticoid pathway") of the zona fasciculata.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, failure to produce sex steroids in these patients results in sexual infantilism and primary amenorrhea in the female (46,XX) and pseudohermaphroditism in the male (46,XY) (17)(18)(19)(20). In addition, impaired production of cortisol − typical of complete 17OHD −, leads to increased ACTH secretion that stimulates overproduction of deoxycorticosterone (DOC) and corticosterone (B) − non-17-hydroxylated steroid intermediates with mineralocorticoid activity −, causing severe hypertension and hypokalemia (2,(21)(22)(23)(24)(25). Although the serum steroid profile has been extensively studied in 17OHD, systematic evaluation of the full urinary steroid metabolite (metabolome) in these patients is limited.…”
mentioning
confidence: 99%
“…Several founder event mutations have been reported in Han populations previously, including c.1935C4A in the GAA gene, 34 c.1517_1525del in the 17OHD gene 35 and c. 1199A4G in the IVD gene. 36 This study represents the largest number of founder event mutation profiles identified so far in Han populations.…”
Section: Selection Of a Marker For Linkage Analysismentioning
confidence: 96%
“…Furthermore, an analysis of 6 cases of 17OHD suggested that age of onset and hypertension severity are not consistent (14). Although there are only a few reports of 17,20-lyase activity in patients with 17OHDs with menstruation, these reports indicate that patients with 17OHD that menstruate have retained 17,20-lyase activity (8,10,15). Thus, the relationship between in vitro enzyme activity and clinical severity remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 46,XY patients have female external genitalia with a blind-ending vagina, and their testes are found in the abdomen or inguinal canal. Some male patients exhibit ambiguous genitalia (8,9).…”
Section: Introductionmentioning
confidence: 99%